The integration of the rehabilitation of psychiatric patients into the Primary Health Care System - N.E. Sokhela; L.R. Uys (AOSIS, 1998)
This study done in rural and semi-urban clinics examined the ability of primary health care nurses in providing rehabilitation of psychiatric patients in the Primary Health Care service. The objectives of the study were to train and evaluate registered nurses' ability to implement rehabilitation to psychiatric patients in the community. Registered nurses were trained over a period of 10 days. Each client who visited the clinic had a rehabilitation plan drawn with the client and family. Families participated in the training of clients while nurses were trained to identify target symptoms, draw a plan to be followed by the client and his family, set rehabilitation goals and the steps to achieve the goals. The project was implemented over a period of 12 months. Records were then reviewed 1 year after implementation and at 18 months to determine the performance of nurses. Evaluation was done per clinic. Each clinic was evaluated and differences were found and where performance was poor, re-education was done. Each clinic was seen as a case. A record review was done to determine the level of rehabilitation based on the following: - identification of target symptoms - plan for the patient - plan for the family - setting of rehabilitation goals - steps to achieve goals - level of vocational rehabilitation